Increasing Police Presence: Examining Race, Ethnicity, and Perceived Neighborhood Disadvantage as Correlates of Support - Metcalfe, Christi (American journal of criminal justice, 2024)
Given its empirical and public support, increasing police presence seems to be a viable preventive policy option for police agencies. However, the theoretical and empirical literature is not clear on whether this support would vary along race/ethnicity and perceived neighborhood disadvantage, which is relevant given that policies of this kind would likely have a greater impact on disadvantaged communities of color. Using survey data from a national sample, we found that racial and ethnic identity were unrelated to support for increased police presence, while perceived neighborhood disorder was related to greater support for police presence. We also found that neighborhood disorder, social cohesion, and informal social control were indirectly related to support for increased police presence through perceptions of police legitimacy and fear of crime, demonstrating some evidence of the overpolicing-underpolicing paradox in disadvantaged communities. Policy implications of these findings are discussed.